2020
DOI: 10.1186/s13104-019-4861-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid direct identification of positive paediatric blood cultures by MALDI-TOF MS technology and its clinical impact in the paediatric hospital setting

Abstract: Objective: Rapid diagnostic tools are imperative for timely clinical decision making, particularly in bacteraemic patients. This study evaluated the performance of a fast, inexpensive novel in house method for processing positive blood cultures for immediate identification of microorganisms by matrix-assisted laser desorption ionization-time of flight mass spectrometry (Vitek MS bioMérieux). We prospectively analyzed the clinical impact of such method on the management of pediatric patients. Result: In total, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…In line with previous studies using a similar approach [ 16 , 24 30 ] it showed in particular excellent performance for gram-negative bacteria, in particular Enterobacterales , P . aeruginos and S .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies using a similar approach [ 16 , 24 30 ] it showed in particular excellent performance for gram-negative bacteria, in particular Enterobacterales , P . aeruginos and S .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies using the combination of BacT/Alert ® BC bottles and the Vitek ® MS mass spectrometer consistently reported a higher rate of correct identifications for gram-negative bacteria (average 90.4%, 95%-CI = [76.5%, 98.5%]) than for gram-positive bacteria (74.9%, 95%-CI = [53.2%, 95.0%]) [ 16 , 24 30 ]. The thicker peptidoglycan layer of the gram-positive cell wall renders these bacteria more resistant to cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of our study include the small number of carbapenem-resistant bacteria available to perform the broth microdilution technique and the lack of an evaluation of the impact of this technique on patient recovery. However, other studies in this context 14 , 26 have shown that our protocol is very promising in that regard.…”
Section: Discussionmentioning
confidence: 77%
“…Our study was conducted over a long period of time and included many samples from patients in routine care. We replaced the use of chemical reagents, common to most techniques, 10 , 13 , 14 , 15 with saline, a solution available in any microbiology laboratory that does not harm the environment or laboratory personnel. The technique was inexpensive, easy to perform, and identification results could be obtained within 15 minutes after positive labeling of the blood culture.…”
Section: Discussionmentioning
confidence: 99%